Simulation of Airflow Patterns and Aerodynamic Forces on a Chambered Airfoil and Symmetric Airfoil with Maximum Thickness Variation - I Gede Kartana; Anak Agung Adhi Suryanwan; I Gusti Ketut Sukadana (Natural Sciences Engineering and Technology Journal, 2023)
Flow across the airfoil can cause drag and lift forces. The difference in pressure between the top and bottom surfaces of the airfoil creates a force that is perpendicular to the flow of fluid, and this force is called the lift force, and parallel to the flow is called the drag force. The author conducted research on simulating airflow patterns across the airfoil with maximum thickness variations. In this research, the simulation method is CFD (Computational Fluid Dynamic) using ANSYS Fluent software. The solution or solver method used in this simulation is the SIMPLE (Semi Implicit Method for Pressure Linked Equation) scheme. The flow pattern is shown by the streamline formed on the symmetric airfoil for α=0°, which will be symmetric, as well as the separation on the two sides, both the upper and lower sides. In contrast to the chambered airfoil, flow separation occurs only on the upper side. This indicates that there will be a pressure difference on the upper side and lower side so that the lift force can occur even though α=0°, because the lower side shows the pressure side. The greater the maximum thickness, the faster flow separation occurs. Then the higher the velocity value, the flow separation will be delayed due to an increase in the momentum of the working fluid flow, which overcomes the shear stress that occurs. At the angle of attack α=0°, the greater the maximum thickness of the chambered airfoil produces a greater lift force, while the symmetric airfoil does not produce lift.